Molecular monitoring of therapeutic milestones and clinical outcomes in patients with chronic myeloid leukemia. Issue 4 (13th November 2018) - Klil‐Drori, Adi J.; Yin, Hui; Azoulay, Laurent; Del Corpo, Alexa; Harnois, Michaël; Gratton, Michel‐Olivier; Olney, Harold J.; Delage, Robert; Laneuville, Pierre; Mollica, Luigina; Busque, Lambert; Assouline, Sarit E.; et al.
Abstract: Background: In the current study, the authors determined whether adhering to molecular monitoring guidelines in patients with chronic myeloid leukemia (CML) is associated with major molecular response (MMR) and assessed barriers to adherent monitoring. Methods: Newly treated patients with CML from the Quebec province‐wide CML registry from 2005 to 2016 were included. Timely polymerase chain reaction (tPCR) was defined as the molecular assessment of BCR ‐ABL1 at the 3‐month, 12‐month, and 18‐month time points from the initiation of tyrosine kinase inhibitor (TKI) therapy. The cohort was analyzed as a nested case‐control study. Cases with a first‐ever MMR ( BCR‐ABL1 ≤0.1%, assessed at any time during follow‐up) were matched to up to 5 controls by duration of TKI therapy, volume of patients with CML at the treatment center, year of cohort entry, and age. Odds ratios (ORs) for the performance of tPCR and MMR were adjusted for sex, comorbidities, type of TKI, and other important covariates. Results: The cohort included 496 patients. Of 392 MMR events, 67.9% occurred before 18 months. The performance of tPCR was associated with a doubling of the MMR rate (OR, 2.23; 95% confidence interval [95% CI], 1.56‐3.21) and was similar with 1 to 3 tPCRs performed ( P = .67). Furthermore, tPCRs at 3 months (OR, 2.77; 95% CI, 1.81‐4.23) and 12 months (OR, 3.00; 95% CI, 1.64‐5.49) were associated with achieving early MMR, whereas tPCRs at 18 months were not (OR, 1.23; 95% CI, 0.80‐1.89). Low‐volume centers were found to have lower adherence to tPCR (OR, 0.60; 95% CI, 0.40‐0.89). Conclusions: Timely molecular assessment at 3 months and 12 months appears to benefit patients with CML. Adherence to timely monitoring should be encouraged, especially in low‐volume treatment centers. Abstract : In the current study, the authors assess whether guideline‐adherent molecular monitoring of therapeutic milestones in patients with chronic myeloid leukemia is associated with clinical benefit. Molecular assessment at approximately 3 months and 12 months appears to be associated with higher rates of early major molecular response.